Mobility and Competitive Action on Competitive Advantage of Indonesian Small Medium Enterprises in the Clothing Industries - ZULTAQAWA, Zeis; ALEXANDRI, Mohammad Benny; RIZAL, Muhammad; KOSTINI, Nenden; AULIA, Muhammad Donie (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The purpose of this study is to find out how mobility and competitive action affect the competitive advantage of SMEs business sector in the clothing industries in Indonesia. This research is based on a quantitative approach using a population of clothing industries in Bandung Regency. Samples are taken with random sampling techniques. Samples are 110 SMEs producing clothing. Data is processed using Descriptive Analysis and Path Analysis. The findings show that mobility has no impact on competitive advantaged but has high impact on competitive action also has a positive effect on competitive advantage in SMEs in Bandung Regency. This research shows that mobility and competitive action can create a competitive advantage in the clothing industries in Bandung Regency although in small impact.